Board Composition, Board Effectiveness, and the Observed Form of Takeover Bids - Bange, Mary M.; Mazzeo, Michael A. (Review of Financial Studies, 2004)
We show that bidding firms consider target board characteristics when deciding takeover offer types and initial offer premiums. We study a sample of 436 proposed negotiated mergers and bypass offers. Firms with individuals holding the titles of both chief executive officer (CEO) and board chair are more likely to receive bypass offers. These offers are more likely to be successful and generate higher target shareholder gains over the takeover offer period. When the target's board is independent, the target is less likely to receive a high premium and the offer is less likely to succeed.